Analisis Pengadaan Kendaraan Dinas Operasional Melalui Sistem Pembelian - Riris, Reskiana; Wardhana, Ananto Krisna (CV. ITTC INDONESIA, 2023)
In carrying out the main duties of the agency, the government requires a procurement system to meet operational needs. One of the procurements carried out is the procurement of operational service vehicles. This research is descriptive qualitative by using data collection techniques through observation, interviews, studying existing documents and conducting case studies in the field to obtain conclusions about the procurement system used and provide suggestions for future program development.The results showed that the two-wheeled service vehicle procurement system through the purchasing system was effective and provided benefits. While the procurement of four-wheeled official vehicles through the purchasing system has not been effective and efficient, therefore an alternative rental system is needed to provide many benefits.